Hyperacusis and Misophonia: A Systematic Review of Psychometric Measures - Kula, Fatma Betul; Cropley, Mark; Aazh, Hashir (Journal of the American Academy of Audiology, 2022)
Background Hyperacusis can be defined as an intolerance of certain everyday sounds, which are perceived as too loud or uncomfortable and which cause significant distress and impairment in the individual's day-to-day activities. Misophonia is defined as a high magnitude of emotional and behavioral reaction to certain sounds produced by human beings, such as eating sounds and breathing sounds. Several psychometric instruments have been developed to assess symptoms and the impact of hyperacusis and misophonia; however, to the authors' knowledge, no study has evaluated and compared the methodological quality of the studies on psychometric properties of the existing instruments.Purpose This article systematically reviews the research studies assessing the psychometric properties of the instruments used for hyperacusis and misophonia and assesses the quality and appropriateness of the methodologies used.Research Design Systematic review.Data Collection and Analysis A systematic literature search was performed using five electronic literature databases (PubMed, Scopus, PsycINFO, Google Scholar, and Web of Science). Studies were included if they were written in English and reported information about the psychometric properties of instruments measuring hyperacusis or misophonia symptoms or their impact. The quality of the studies and that of the psychometric instruments were evaluated using the consensus-based standards for the selection of health-measurement instruments (COSMIN) tool.Results The title and abstracts of 916 articles were screened and 39 articles were selected for full-text evaluation, with 14 articles meeting the inclusion criteria. From these 14 articles, 8 different instruments (5 for hyperacusis and 3 for misophonia) were identified and reviewed comprising: (1) Hyperacusis Questionnaire (HQ), (2) Inventory of Hyperacusis Symptoms, (3) questionnaire on hypersensitivity to sound, (4) Hyperacusis Handicap Questionnaire, (5) short HQ, (6) Amsterdam Misophonia Scale, (7) MisoQuest, and (8) the Misophonia Questionnaire.Conclusion None of the papers reviewed reported all the information required to meet the COSMIN standards. The studies' methodological quality varied between “very good” and “inadequate” depending on their grade on the COSMIN tool. There is a need for further research on the psychometric properties of the instruments included in this review.
Keywords: hyperacusis; misophonia; psychometric instruments and properties